The essence of enterprise’s sales potential of an innovation and it dependence on a market demand - Strunina, Lesia (My University, 2016)
There are considered main internal and external impact factors on possibility of sales of an innovation in the article. It is determined an interrelation of market consumption potential and volumes of sales of the innovation by the enterprise. It is offered a method of calculation sales potential of the innovation depending on company’s position on the market. У статті розглянуто основні внутрішні та зовнішні чинники впливу на можливості реалізації інновації. Визначено взаємозв'язок між споживчим потенціалом ринку та обсягами реалізації інновації підприємством. Запропонований метод розрахунку потенціалу реалізації інновації залежно від позиції компанії на ринку.
Keywords: marketing of innovations; збут інновацій; innovative activity of the enterprise; інноваційна діяльність підприємства; потенціал збуту інновації; кафедра економіки праці та менеджменту